Real‐life study of safety of thiopurine‐allopurinol combination therapy in inflammatory bowel disease: myelotoxicity and hepatotoxicity rarely affect maintenance treatment. Issue 4 (30th July 2019) - Kreijne, Joany E.; de Veer, Rozanne C.; de Boer, Nanne K.; Dijkstra, Gerard; West, Rachel; Moorsel, Sofia A. W.; de Jong, Dirk J.; van der Woude, C. Janneke; de Vries, Annemarie C.; ,
Summary: Background: Low‐dose thiopurine‐allopurinol (LDTA) combination therapy is a commonly applied optimisation strategy in IBD patients with a skewed thiopurine metabolism. Aim: To assess continued LDTA maintenance treatment at annual intervals and explore risk factors for treatment cessation Methods: Adult IBD patients treated with LDTA between 2009 and 2016 were retrospectively included. Data on the incidence of clinical and laboratory adverse events (AEs), including hepatotoxicity and myelotoxicity resulting in imposing LDTA therapy cessation and associated risk factors were collected. Results: In total, 221 IBD patients (46% male, median age 42 years) were included. Maintenance LDTA treatment was continued in 78% of patients at 1 year (n = 145), 66% at 2 years (n = 83), 57% at 3 years (n = 52) and 52% at 4 years (n = 33). Treatment in patients receiving LDTA therapy for AEs during thiopurine monotherapy was more often continued than in patients initiating LDTA for other indications (eg, ineffectiveness of thiopurine monotherapy, routinely discovered skewed metabolism) ( P  = 0.016). Myelotoxicity during thiopurine monotherapy resolved in 87% and hepatotoxicity in 86% after median of 1.2 and 1.4 months after LDTA initiation. Cumulative incidence of AEs during LDTA resulting in therapy cessation within total follow‐up of 449 treatment‐years was 7% for clinical AEs, 4% for myelotoxicity and 1% for hepatotoxicity. Conclusion: LDTA therapy is a safe and beneficial optimisation strategy in IBD patients. Continued maintenance LDTA treatment is 52% after 4 years of treatment and most commonly affected by ineffectiveness of LDTA rather than LDTA‐attributed toxicity. LDTA optimisation strategy is most advantageous in patients failing thiopurine monotherapy due to AEs.